2008
DOI: 10.1007/s11465-008-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of meso-scale milling machine tool and its performance analysis

Abstract: To overcome the shortcomings of current technologies for meso-scale manufacturing such as MEMS and ultra precision machining, this paper focuses on the investigations on the meso milling process with a miniaturized machine tool. First, the related technologies for the process mechanism studies are investigated based on the analysis of the characteristics of the meso milling process. An overview of the key issues is presented and research approaches are also proposed. Then, a mesoscale milling machine tool syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Many academic institutions, mainly in Europe and Asia, have been directing efforts toward the development and commercialization of smaller, even desktop-sized micro-cutting machines. These efforts have resulted in a number of compact, three to five-axis, mainly micromilling machines [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Machinery For Micromillingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many academic institutions, mainly in Europe and Asia, have been directing efforts toward the development and commercialization of smaller, even desktop-sized micro-cutting machines. These efforts have resulted in a number of compact, three to five-axis, mainly micromilling machines [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Machinery For Micromillingmentioning
confidence: 99%
“…[123]), whose findings are confirmed with experimental results [124], define a reference stress as a criterion for elastic failure. For the plane stress condition Tresca's reference stress is defined as [80]: 13) and von Mises' reference stress as:…”
Section: Isotropic Modelingmentioning
confidence: 99%
“…Most of these components fall into the scales from ten microns to one millimeter, which is known as mesoscale in mechanical engineering. Current trends toward product miniaturization require fabrication techniques that can efficiently and economically produce mesoscale components with complex microfeatures over a wide range of material types [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most researches revealed that the size effect, cutter edge radius and minimum undeformed chip thickness in micro machining (milling, turning etc.) has similar effects on micro grinding process [7]. Ohbuchi and Obikawa [8] investigated the surface generation of grinding considering the grit shape and cutting speed.…”
Section: Introductionmentioning
confidence: 99%